Phytochemical and chemotaxonomic study of Polygala altomontana (Polygalaceae). (April 2018) - Tizziani, Tiago; Venzke, Dalila; Ruani, Ana Paula; Pereira, Marcos; Micke, Gustavo Amadeu; Pizzolatti, Moacir Geraldo; Brighente, Inês Maria Costa
Abstract: In this study, 7 compounds were isolated from a hydroalcoholic extract of Polygala altomontana : aurapten (1 ), α-spinasterol (2 ) dihydrostyryl-2-pyrone (3 ) and styryl-2-pyrones (4 –7 ). The styryl-2-pyrone (5 ) is new in the literature and although the others are known compounds this is the first time they have been isolated from the species P. altomontana . This is the second species of the genus Polygala to present the accumulation of dihydrostyryl-2-pyrones and styryl-2-pyrones. The chemotaxonomic significance of this data for the Polygala genus was summarized. Highlights: The isolation of seven compounds from Polygala altomontana is reported for the first time. A newly identified styryl-2-pyrone as 4-methoxy-6-(11, 12-methylenedioxy-10-methoxystyryl)-2-pyrone is described. P. altomontana is the second species of the genus Polygala to present the accumulation of styryl-2-pyrones.